Thioimidates as Versatile Building Blocks: Synthesis and Their Applications - Swaroop, Toreshettahally R.; Umashankara, Muddegowda; Rangappa, Kanchugarakoppal S. (Recent Developments in Chemistry and Biochemistry Research Vol. 5, 2024)
We outline herein the protocols developed to synthesize a diverse array of organic compounds: from carbimidothioates, we successfully synthesized \(β\)-enaminones, 1,5-diaryl-1H-tetrazoles, and 1,3,4-oxadiazoles, each of which has potential applications in various fields including pharmaceuticals and materials science. From carbamimidothioates, our synthesis yielded both imidazoles and 1,5-disubstituted tetrazoles, thus expanding the scope of these nitrogen-rich heterocycles in medicinal chemistry. Additionally, the transformation of 2-oxo-ethanimidothioates into 2-amino-3-aryl-quinoxalines highlights a novel pathway for producing compounds that could be valuable in light-emitting devices and as pharmacological agents. This detailed investigation not only advances the field of synthetic organic chemistry but also sets the stage for future innovations in the synthesis and application of heterocyclic compounds.